Reduction for ordinary and partial differential equations by using lie group - Husayn, Iman Ali; Ulwan, Zaynab Muhammad (Majallat Jāmiʻat Bābil, 2019)
In this publication, We have done Lie group theory is applied to reduce the order of ordinary differential equations (ODEs) with 1-parameter and reduce a PDEs to ODEs . Also set up algorithm to solve ODEs and PDEs to obtain the exact solution